Design and Build a Safe Security System Using RFID With e-KTP as a Tag and Monitoring With IoT-Based Esp32-Cam With Telegram Notifications: Rancang Bangun Sistem Pengaman Brankas Menggunakan RFID Dengan e-KTP Sebagai Tag dan Monitoring Dengan Esp32-Cam Berbasis IoT Dengan Notifikasi Telegram - Ashar, Abdul Adim; Saputra, Dwi Hadidjaja Rasjid (Indonesian Journal of Innovation Studies, 2021)
Security is one form of convenience to protect archives or important objects such as land certificates, BPKB, and many others, and as a place to store these items a safe is created, with the development of technology, the safe is combined with several electronic components, a modern safe is created without a conventional key, only uses radio frequency identification which is already supported with an E-KTP and password to open it, uses a PIR sensor and an esp32 camera to find out who will access the safe and can be monitored every time. time via a smartphone using the telegram application, and also the telegram application can control the alarm if something suspicious is seen from the esp32 camera.